Case Report: A novel approach to pseudoportomesenteric hypertension with refractory chylothorax and ascites - Sakiri, Ahmet; De Marco, Annalise; Patel, Shreekar; Khan, Naser; Hamoudah, Thayer; Dawood, Altaf; Kakarla, Rajesh (Frontiers in Gastroenterology, 2025)
Pseudoportomesenteric hypertension (PPMH) is a rare form of non-cirrhotic portal hypertension caused by increased pressure in the portal and mesenteric venous systems. Unlike traditional portal hypertension, which arises from liver cirrhosis, PPMH stems from conditions that are extrahepatic in etiology, such as venous thrombosis, external compression by intra-abdominal masses, or congenital anomalies. Treatment is aimed at addressing the underlying cause of obstruction. We report a case of PPMH secondary to a pancreatic neuroendocrine tumor (PNET). A female in her 60s presented with a six-month history of diarrhea, 30-pound weight loss, and dyspnea. Initial evaluation revealed massive right pleural effusion with subtotal lung collapse, cardio-mediastinal shift, and sub-segmental pulmonary emboli. Additionally, she had extensive four-quadrant ascites and a heterogeneous mass at the pancreatic head and uncinate process encasing the superior mesenteric artery (SMA), with mass effect on the superior mesenteric vein (SMV). The patient developed refractory ascites and chylothorax, which were managed with a chest tube and abdominal drain placement. Retroperitoneal lymph node biopsy confirmed a well-differentiated grade 2 primary PNET. Following a multidisciplinary assessment, the patient underwent stent placement in the SMV. Initial trans-hepatic portal venography showed a portal vein pressure of 12 cm H2O and a significantly elevated SMV pressure of 32 cm H2O, indicating severe obstruction at the portal-mesenteric confluence. Extensive mesenteric collateralization and large duodenal and mesenteric varices were noted. Angioplasty and stenting of the SMV were performed, resulting in a 10 cm H2O reduction in the pressure gradient, improved antegrade hepatopetal flow, and resolution of varices. This case highlights the importance of recognizing extrahepatic causes of portal hypertension, particularly in patients with malignant tumors, and the role of palliative endovascular interventions in managing the sequelae of PPMH.